2015
DOI: 10.1631/jzus.b1500067
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation level of promoter region of activating transcription factor 5 in glioma

Abstract: Abstract:Transcription factors, which represent an important class of proteins that play key roles in controlling cellular proliferation and cell cycle modulation, are attractive targets for cancer therapy. Previous researches have shown that the expression level of activating transcription factor 5 (ATF5) was frequently increased in glioma and its acetylation level was related to glioma. The purposes of this study were to explore the methylation level of ATF5 in clinical glioma tissues and to explore the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…However, the cohorts underlying the assessment of ATF5 expression in GBM were too small to define clinical subgroups 23,25. Furthermore, reports on LGA are scarce, comprising only few specimens and merging different WHO grades and tumor entities into the same group for further analysis,26 which limits the scientific significance. Therefore, we extended these observations by examining a large panel of 79 GBM, 40 LGA, and 10 NB for ATF5 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the cohorts underlying the assessment of ATF5 expression in GBM were too small to define clinical subgroups 23,25. Furthermore, reports on LGA are scarce, comprising only few specimens and merging different WHO grades and tumor entities into the same group for further analysis,26 which limits the scientific significance. Therefore, we extended these observations by examining a large panel of 79 GBM, 40 LGA, and 10 NB for ATF5 expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, such interference did not cause any visible effects on NB or cultured astrocytes 21,23,24. Although data concerning ATF5 expression in GBM are available,23,25 data on ATF5 expression in LGA are scarce 26. ATF5 has been shown to be significantly upregulated especially in invasive ductal and invasive lobular breast carcinomas,27 and its overexpression enhances the migratory and invasive behavior of A549 lung carcinoma cells 28.…”
Section: Introductionmentioning
confidence: 99%
“…It could be hypothesized that these functions mediated by ATF5 in cancer also occur in nontransformed cells, but this hypothesis has yet to be tested. ATF5 expression is also significantly associated with tumor grade in several cancer types [ 48 , 49 ]. In addition to these functions is the novel role for ATF5 as a structural protein where it facilitates formation of the centrosome, thereby suggesting ATF5 may promote proper mitotic function [ 50 ].…”
Section: Role Of Atf5 In the Development Of A Diverse Range Of Cancermentioning
confidence: 99%
“…ATF5 expression was also shown to be upregulated in GBMs and anaplastic gliomas relative to low grade gliomas and normal cortical tissue, indicating that ATF5 expression may be associated with more malignant glioma phenotypes [ 53 ]. Indeed, analysis of ATF5 promoter methylation in glioma revealed that there is a substantial decrease in promoter methylation in high grade gliomas relative to low grade gliomas and normal tissue, thereby suggesting alterations in promoter methylation drive aberrant ATF5 expression in high grade gliomas [ 49 ]. In addition, ATF5 was shown to mediate the survival response to serum deprivation and staurosporine treatment in C6 glioma cells supporting the notion that ATF5 has an oncogenic and prosurvival role in gliomas [ 33 ].…”
Section: Gliomamentioning
confidence: 99%
“…In the human genome, there are approximately 30,000 CpG islands. Importantly, approximately 60–70% of annotated gene promoters are associated with CpG islands, suggesting that methylation of CpG islands is an important component of gene expression regulation [16]. The relationship between non-mutagenic environmental factors, influencing epigenetics alteration and subsequently pathology, has been examined primarily through the studies of the DNA methylation pattern in animal models [17].…”
Section: Epigenetic Predisposition For Ra Development With Particumentioning
confidence: 99%